2016
DOI: 10.1007/s00520-016-3511-9
|View full text |Cite
|
Sign up to set email alerts
|

Estimating prevalence of functional iron deficiency anaemia in advanced cancer

Abstract: PurposeAnaemia is a common complication of cancer causing symptoms including fatigue. It is also associated with shorter survival. Cancer causes systemic inflammation which interrupts iron metabolism leading to a functional iron deficiency (FID). There are few data on prevalence or aetiology of anaemia in those with advanced cancer. We aimed to establish the prevalence of anaemia and estimate extent of FID anaemia in patients with advanced cancer. MethodsAll patients with advanced cancer referred to two UK spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
21
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 19 publications
3
21
0
3
Order By: Relevance
“…Anaemia is a common complication of cancer and is more common in advanced disease. In a cohort of 1797 patients with advanced cancer referred to palliative care services, we found that 38% had moderate to severe anaemia and that functional iron deficiency was present in 39%–43% 1. Anaemia can cause symptoms including fatigue and breathlessness, with fatigue being the most frequently reported symptom in cancer 2…”
Section: Introductionmentioning
confidence: 99%
“…Anaemia is a common complication of cancer and is more common in advanced disease. In a cohort of 1797 patients with advanced cancer referred to palliative care services, we found that 38% had moderate to severe anaemia and that functional iron deficiency was present in 39%–43% 1. Anaemia can cause symptoms including fatigue and breathlessness, with fatigue being the most frequently reported symptom in cancer 2…”
Section: Introductionmentioning
confidence: 99%
“…Anemia é uma complicação comum em pacientes com câncer e causa diversos sintomas como fadiga e falta de ar. Neoh et al (2017)…”
Section: Introductionunclassified
“…[6][7][8] Patients with advanced cancer are likely to have FID as the predominant etiology of anemia. 9 ID anemia is also associated with shorter survival times in some types of cancers, including colon cancer, lung cancer, and breast cancer. [10][11][12] Notably however, little is known about ID in NB patients.…”
mentioning
confidence: 99%